ANALISIS PERLAKUAN AKUNTANSI DAN PELAPORAN PERTANGGUNGJAWABAN SOSIAL PADA PT. ANGKASA PURA I (PERSERO) CABANG BANDAR UDARA INTERNASIONAL SAM RATULANGI MANADO - Belda, Tumilantouw Frety Emma; Manossoh, Hendrik; Rondonuwu, Sintje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Companies need a response that positively by public because the comunnity constitutes one of the elements that can determine success business an entity. Accounting social responsibility is very powerful tool for the company in expressing social activities. The purpose of this study is to find out how accounting treatment and reporting corporate social responsibility in accordance with UU. No. 40 Tahun 2007, Peraturan Menteri BUMN No. 5/MBU/2007 and financial accounting standards. Data collection methods in this study are interviews and document review. Data analysis method of this research is Miles and Huberman, which compares the company’s procedures with existing theories. The result shows that the accounting treatment and reporting in PT. Angkasa Pura I (Persero) has basically been fitted with financial accounting standards, UU No. 40 Tahun 2007, and Peraturan Menteri BUMN No.5/MBU/2007, but a company should make separate reports about the realization of activities to ease evaluate program that will be implemented.Keywords: accounting treatment, corporate social responsibility, partnerships and community development program